1986
DOI: 10.1080/02652038609373601
|View full text |Cite
|
Sign up to set email alerts
|

Lead in alcoholic beverages

Abstract: Following the finding that blood lead concentrations in middle-aged men were positively associated with alcohol consumption, the Royal Commission on Environmental Pollution recommended that information on lead in alcoholic beverages be obtained. The results reported here were obtained in response to the Royal Commission's request. About 90% of canned and bottled beers contained less than or equal to 10 micrograms/l of lead, whereas nearly half the draught beers sampled contained greater than 10 micrograms/l an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 3 publications
3
22
1
Order By: Relevance
“…Several investigators have concluded that among regular wine drinkers, lead intake from wine may exceed that from diet, water, air, and dust combined (23,24,27,28). We concur, and conclude that for a 70-kg subject, a single Change in blood lead after ingestion of sherry containing 1.21 pmol/Pb/70 kg body weight.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Several investigators have concluded that among regular wine drinkers, lead intake from wine may exceed that from diet, water, air, and dust combined (23,24,27,28). We concur, and conclude that for a 70-kg subject, a single Change in blood lead after ingestion of sherry containing 1.21 pmol/Pb/70 kg body weight.…”
Section: Discussionsupporting
confidence: 63%
“…Epidemiologic studies have found a dose-response relationship between alcohol consumption and BPb (18)(19)(20)(21)(22); wine consumption has been reported as a specific risk factor (18,19). This is not surprising as lead concentrations in wines reportedly range from 0.14 to 1.21 pmol/l, with a mean of 0.42 pmol/l (23).…”
Section: Discussionmentioning
confidence: 94%
“…Surprisingly, we have failed to detect a signifi cant change in iron, copper, zinc, and selenium levels, in contradiction to earlier indications (Arinola, 2008;Cook et al, 1991;González-Reimers et al, 2010;Skalny, 1990;Skalny and Skosyreva, 1987;Zarski et al, 1985). Earlier studies also demonstrated that certain alcoholic drinks may be contaminated with toxic trace elements (Sherlock et al, 1986). At the same time, we did not observe a signifi cant increase in heavy metal levels in either maternal or cord blood.…”
Section: Discussionsupporting
confidence: 42%
“…In comparison, the average lead concentrations in beers (n=9) produced and consumed in Finland, was reported as 9µg/L and the cadmium concentrations were bellow 1µg/L [13]. In United Kingdom, the analyses of 302 samples of beer indicated a range of less than 10µg Pb/L to over 200µgPb/ L [12]. Spanish beers (n=8) have shown values from 3 to 15µgPb/L [1] and Italian beers (n=7) from less than 30 to 120µgPb/L [5].…”
Section: Number Of Replicates =mentioning
confidence: 99%